Proceedings of the 7th Annual Conference on Genetic and Evolutionary Computation 2005
DOI: 10.1145/1068009.1068094
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cooperative co-evolutionary dynamics via simple fitness landscapes

Abstract: Cooperative co-evolution is often used to solve difficult optimization problems by means of problem decomposition. Its performance for such tasks can vary widely from good to disappointing. One of the reasons for this is that attempts to improve co-evolutionary performance using traditional EC analysis techniques often fail to provide the necessary insights into the dynamics of co-evolutionary systems, a key factor affecting performance. In this paper we use two simple fitness landscapes to illustrate the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…Additionally, although this paper has focused on cooperative setups, our previous work (Popovici and De Jong, 2004;Popovici and De Jong, 2005b) showed that the methods described here can be used to gain insights into competitive co-evolution as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, although this paper has focused on cooperative setups, our previous work (Popovici and De Jong, 2004;Popovici and De Jong, 2005b) showed that the methods described here can be used to gain insights into competitive co-evolution as well.…”
Section: Discussionmentioning
confidence: 99%
“…This technique was first introduced in (Popovici and De Jong, 2004) and has been improved since then. We have already successfully used it to gain insight into the way co-evolutionary algorithms work, both in competitive (Popovici and De Jong, 2005b) and cooperative setups (Popovici and De Jong, 2005a;Popovici and De Jong, 2005c). In this paper we describe this technique and use it to extend our previous results.…”
Section: The Importance Of Co-evolutionary Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is in contrast to other works employing mathematical functions as a test-bed for the study of evolutionary approaches. Particularly for the case of coevolutionary algorithms, mathematical functions based on few independent variables are usually employed [17,13], decomposing the overall problem in few and very simple entities. However, this approach can not reveal the power of each algorithm and its capability to address difficult problems.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly the approach followed by coevolutionary algorithms which utilize separate populations to evolve partial entities of the problem [14,17]. In order to formulate a composite problem solution, individuals within different populations have to be selected, put together and operate in parallel [1,13]. Each population can use its own evolutionary parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%